2016
DOI: 10.1371/journal.pone.0169186
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Vesicles Released by a hypervesiculating Escherichia coli Nissle 1917 tolR Mutant Are Highly Heterogeneous and Show Reduced Capacity for Epithelial Cell Interaction and Entry

Abstract: Membrane vesicles (MVs) produced by Gram-negative bacteria are being explored for novel clinical applications due to their ability to deliver active molecules to distant host cells, where they can exert immunomodulatory properties. MVs released by the probiotic Escherichia coli Nissle 1917 (EcN) are good candidates for testing such applications. However, a drawback for such studies is the low level of MV isolation from in vitro culture supernatants, which may be overcome by the use of mutants in cell envelope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 57 publications
5
34
0
Order By: Relevance
“…BLP by itself on the outer membrane side is not sufficient, given that its ability to bend and tilt enables significant deviation in the cell-wall position. This agrees with experimental studies that showed that mutations in either the tolR or the ompA gene destabilized the cell envelope, resulting in the formation of outer membrane vesicles in E. coli (Deatherage et al, 2009;Perez-Cruz et al, 2016).…”
Section: Tolr-peptidoglycan Interactions When Ompa Is Truncatedsupporting
confidence: 91%
“…BLP by itself on the outer membrane side is not sufficient, given that its ability to bend and tilt enables significant deviation in the cell-wall position. This agrees with experimental studies that showed that mutations in either the tolR or the ompA gene destabilized the cell envelope, resulting in the formation of outer membrane vesicles in E. coli (Deatherage et al, 2009;Perez-Cruz et al, 2016).…”
Section: Tolr-peptidoglycan Interactions When Ompa Is Truncatedsupporting
confidence: 91%
“…OMVs have also been tested as delivery vehicles for targeted gene silencing using siRNA-packaged OMVs (Alves et al, 2016), although the exact mechanism for packaging proteins and other reagents in OMVs still remains to be fully understood. There is also an increasing interest in identification of OMV sub-populations (Pérez-Cruz et al, 2016; Bonnington and Kuehn, 2017; Turner et al, 2018; Cooke et al, 2019; Toyofuku et al, 2019; Zavan et al, 2019), as well as in assessing the importance of OMV size for cellular uptake and entry (Turner et al, 2018). Therefore, changes observed here in the NTA spectra of OMVs in response to PAD inhibitor treatment (Figures 1D–G) may be of some interest in addition to the observed reduction in total amounts of OMV/MVs released.…”
Section: Discussionmentioning
confidence: 99%
“…To help determine the mechanism of the bacteriocin delivery that leads to growth inhibition of L. delbrueckii by L. acidophilus MVs, membrane fusion was investigated by DiO [DiOC 18 (3) (3,3dioctadecyloxacarbocyanine perchlorate] staining. DiO was used previously for tracking of E. coli and Pseudomonas aeruginosa OMV internalization into cells (Perez-Cruz et al, 2016;Alves et al, 2017;Bitto et al, 2017), by binding specifically to MV Figure 9A and Supplementary Figure S1), suggesting fusion and incorporation of DiO from L. acidophilus MVs into the membrane of L. delbrueckii, where the contents of the MVs are likely transferred into the cell.…”
Section: Membrane Fusion Of L Acidophilus Mvs and L Delbrueckiimentioning
confidence: 92%